Sports Human Resources Development (Human Resources Management Survey in Petanque Sport Branch, Surakarta City) - Sri Wijiastuti; Zandra Dwanita Widodo; Fatkhul Imron; Kodrad Budiyono (International Journal of Asian Business and Management, 2023)
The existence of sports human resources in the petanque sport in Surakarta City, competency development in various ways is needed so that human resources in petanque sports in Surakarta City can be competent in completing their main tasks and functions. The aims of this study were to: (1) Know and describe the flow and process of sports human resource management in the petanque sport in the city of Surakarta. (2) Knowing and describing the potential of sports human resources in the petanque sport in Surakarta City. In this study the method used is descriptive qualitative with an inductive approach. The sample used. Data collection techniques used in this study were interviews, observation, questionnaires and document collection. Data analysis used interactive analysis includes data reduction, data presentation and drawing conclusions and verification. The findings from the research conducted included: (1) The sports human resource management process carried out by Petanque Surakarta City has fulfilled the provisions of the running of the organization, namely processes in the form of planning, organizing, directing and supervising. (2) The potential of Human Resources for the Petanque Sport in Surakarta City in general has not been optimally developed. This can be seen from the results of the data obtained from several indicators, namely the number of Sports Human Resources, qualifications, involvement in activities, achievements and welfare of the Surakarta City Petanque